Keris dalam Budaya Minangkabau : “Visualisasi Nilai Kepemimpinan Pangulu” - Muhsin Ilhaq (Besaung : Jurnal Seni Desain dan Budaya, 2021)
AbstractKris is one of the noble cultural art works of past cultural heritage that has high value, its usefulness always develops from time to time according to the age context. Initially the kris developed in Java as a traditional weapons system, then spread to various regions of the archipelago including the Minangkabau. Almost the entire archipelago has a kris culture, although there are differences in names, forms and functions in each region. These differences encourage the desire to understand the meaning and value of the kris in accordance with the context of Minangkabau culture. Overall, the kris is a form of physical culture that reflects the values of goodness, especially related to Pangulu's leadership in Minangkabau.Keywords : Kris, Minangkabau Cultur, Leadership Value Abstrak Keris merupakan salah satu karya seni budaya adiluhung peninggalan budaya masa lalu yang bernilai tinggi, kegunaannya selalu berkembang dari masa ke masa sesuai konteks zaman. Awalnya keris  berkembang di Jawa sebagai sistem senjata tradisional, kemudian menyebar ke berbagai wilayah Nusantara termasuk ke Minangkabau. Hampir seluruh wilayah nusantara memiliki budaya keris, meskipun terdapat perbedaan nama, bentuk maupun fungsinya di tiap wilayah.Perbedaan tersebut mendorong keinginan untuk memahami makna dan nilai keris sesuai dengan konteks budaya Minangkabau.Secara keseluruhan, keris merupakan wujud budaya fisik yang mencerminkan nilai-nilai kebaikan, terutama terkait dengan kepemimpinan Pangulu di Minangkabau.Kata kunci : Keris, Budaya Minangkabau, Kepemimpinan